Towards biomimetic electronics that emulate cells. (September 2020) - Lubrano, Claudia; Matrone, Giovanni Maria; Forro, Csaba; Jahed, Zeinab; Offenhaeusser, Andreas; Salleo, Alberto; Cui, Bianxiao; Santoro, Francesca
Abstract: Abstract : Bioelectronics aims to design electronic devices which can be fully integrated within tissues to monitor or stimulate specific cell functions. The main challenge is the engineering of the cell–chip interface and diverse materials, and devices have been developed to recapitulate biological architectures and functionalities. In this Prospective article, the authors give an overview on how the bioelectronics community has exploited biomimetic approaches to emulate cell morphologies, interactions, and functions to design optimal electrical platforms to be coupled to living cells.